Effects of Salinity on Spawning and Early Development of the Tube-Building Polychaete Hydroides elegans in Hong Kong: Not Just the Sperm's Fault? - Pechenik, Jan A.; Pearse, John S., 1936-; Qian, Pei-Yuan. (Tufts University. Tisch Library., 2017)
Ambient salinities drop dramatically during monsoon season in Hong Kong coastal waters, posing a number of problems for externally fertilizing species like the polychaete Hydroides elegans. In this study, we investigated (1) whether adults would retain their gametes when external salinity dropped to levels too low to support fertilization and development, and (2) whether failure of development at low salinity reflects a failure of fertilization or a failure of fertilized eggs to cleave. Adults released eggs and sperm in the laboratory even at the lowest salinity tested, a practical salinity (S) of 5, and yet very few eggs cleaved at salinities below about 22. By mixing gametes at high salinity and then transferring the fertilized eggs to low-salinity seawater, we found that salinities below about 22 reduced the percentage of fertilized eggs that cleaved. Similarly, mixing gametes at salinities as low as 15 and then transferring the eggs to full-strength seawater (S = 30) rescued a substantial number of eggs, many more of which cleaved after their transfer to the higher salinity. The results suggest that failure of early development at low salinity in this species in large part reflects an inability of newly fertilized eggs to complete meiosis and cleave, rather than simply a failure of fertilization.